Microwave-Assisted Preparation of Magnetic Citric Acid-Sugarcane Bagasse for Removal of Textile Dyes - Nguyen Thi Hong Anh; Tran Thanh Phuc; Tran Nguyen Minh An; Pho Quoc Hue; Nguyen Van Cuong (Indonesian Journal of Chemistry, 2020)
Wastewater from industries has been a serious issue that both manufactures and authorities raise concerns since it brings tremendous demerits to the surrounding environment and human well-being. Therefore, an appropriate treatment method should be applied before being discharged into the environment. In this paper, sugarcane bagasse was modified with citric acid and then used to load the suspension of Fe3O4 nanoparticles to form a nanocomposite of magnetic citric acid-modified sugarcane bagasse. The properties of prepared materials were investigated by a variety of modern methods such as X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FT-IR), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM) and a Vibrating sample magnetometer (VSM). The adsorptive capacity of prepared materials was investigated with methylene blue as the typical adsorbate. The decolonization effectiveness was increased with increasing contact time and declined with rising initial dye concentration. The higher removal efficiency was observed for the basic medium in comparison with the acidic medium. Additionally, the results showed that more than 12.42 mg/g (98%) of cationic yellow 51, and basic red 46 dyes were removed after 30 min.